The Effect of Organizational Climate and Compensation on Job Satisfaction and Employee Performance - Deni Suryana (Indonesian Journal of Multidisciplinary Science, 2023)
In banking activities and the financial services industry, the contribution of banks to the financial services industry in supporting economic activities is very large, in the midst of very tight and competitive competition banks need innovation and the right strategy to ensure their business continuity and their existence in increasing their business achievement figures, the challenge is getting bigger after it is declared that there are no more restrictions on activities and the return of normal activities back to normal.  This research intends to obtain empirical evidence related to the consequences between organizational climate variables and compensation, in relation to job satisfaction and employee performance.  This research was conducted at Bank Mega Regional Banjarmasin and only analyzed the direct and indirect influence between organizational climate variables (X1), compensation (X2), on job satisfaction (Y1) and employee performance for the period September 2022 to January 2023. The population in this study is employees who are directly on duty with Bank Mega Regional Banjarmasin (direct staff). The sample of this study is the population, namely all employees who work directly at Bank Mega Regional Banjarmasin totaling 240 people who are all employees of Bank Mega Kalimantan who are not outsourced or direct employees of Bank Mega. The source of data used in this research is questionnaires. Information analysis in this research uses Structural Equation Modeling (SEM) with Smart PLS (Partial Least Square) application.  The results of this study show that organizational climate and compensation have a positive effect on employee performance there.